EXTENT OF COMMUNITY PARTICIPATION IN THE MANAGEMENT OF PUBLIC SECONDARY SCHOOLS IN SOUTH-EAST OF NIGERIA - Enyi, Chinwe (International Journal of Psychosocial Rehabilitation, 2021)
Given the various challenges confronting governments and educational administrators in the management of schools, and the need to look for alleviating alternatives, this study investigated the extent of community participation in managing public secondary schools in South East States. Three research questions and two hypotheses guided the study, while data were collected from a sample of 500 principals, using a 15-item researcher designed questionnaire. A stratified proportionate random sampling technique was used to draw the study sample, while descriptive and inferential statistics were used to analyse the collected data. Major findings reveal that communities participate to a “great extent” in funding many school projects and also in providing various infrastructural facilities. Accordingly, it was recommended, among other things, that organizers and mobilizers of community support for education, should focus on the various areas communities have shown interest.